Adaptive Ai Defenses: Bridging Machine Learning and Cybersecurity for Next-Generation Threats - Md Ismail Jobiullah (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The various changes in cyber threats have made the old security systems to be more ineffective in reducing advanced attacks. Since the adversaries adapt, evade, and employ artificial intelligence (AI) and machine learning (ML) to establish adaptive and evasive methods, intelligent self-achieving defense is urgent. This article discusses the incorporation of AI adaptation frameworks into cybersecurity systems to battle the future-generation threats. Exploiting a comprehensive overview of existing ML research and practical deployments, the paper points to the superiority of reinforcement learning, adversarial ML, federated learning, and deep neural networks in building resilience against zero-day attacks, malware, phishing, and advanced persistent threats. An adaptation of this conceptual framework to the domain of adaptive AI defenses is advanced, with modeling of how continual model learning may enable the defender to close the gap between static defensive strategies and changing threats. In evidence-based case performance comparisons, adaptive AI-based systems can do better job in detecting with high accuracies, low false positives and scalability compared to conventional technologies. Concerns about adversarial manipulation, ethical issues, and computational requirements, as well as the provision of future paths, which consist of explainable AI, Policies, and quantum-computing based AI integration are other issues that are discussed in the discussion. This paper can therefore confidently draw adaptive AI defenses as one of the fundamental capabilities of safeguarding online infrastructures in view of the ever-evolving cybersecurity environment. DOI: https://doi.org/10.17762/ijisae.v12i23s.7826